Hierarchical tetramodal-porous architecture of zinc oxide nanoparticles microfluidically synthesized via dual-step nanofabrication - Jin, Su Eon; Hwang, Sung Joo; Jin, Hyo Eon (Materials and Design, 2022)
Zinc oxide (ZnO) nanoparticles (NPs) have been underscored as emerging functional materials in biomedical research domains. In the present study, we generated ZnO NPs to form a hierarchical tetramodal-porous three-dimensional (3D) architecture by immobilization on a solid plate, which helps enhance mass transfer and reaction rate. ZnO NPs were microfluidically synthesized and further solidified via dual-step nanofabrication. The physicochemical properties of as-synthesized ZnO NPs and the aggregates were characterized. Specifically, intraparticle pores in ZnO NPs displayed interconnected cylindrical channels with bimodal distribution centered at 1.3 and 2.0 nm. Mesopores of ZnO NPs were also analysed at 19.5 nm. ZnO NPs were immobilized on silicon wafer and cellulose paper sheet by a simple and reproducible self-assembly, creating hierarchical tetramodal-porous architecture of intra- and inter-particle pores. In the architecture, macropores were detected at 1.2 μm on silicon wafer and 134.62 nm on cellulose paper depending on ethanol wetting of NPs at drying temperature for solvent evaporation. From the results, the ZnO NPs can be unprecedented bioinks in biomedical applications including biocompatible battery electrodes, biosensing, nanobiomedicines, medical devices, cosmetics, and tissue engineering. They can also offer further intriguing theoretical and experimental investigations of multi-modality for hierarchical porosity.
Keywords: Bioink; Biomedical research; Cellulose papers; Dual-step nanofabrication; Hierarchical porosity; Porous architectures; Research domains; Synthesised; Three-dimensional architecture; Zinc oxide nanoparticles; Bioinks; Dual-step nanofabrication; Hierarchical porosity; Three-dimensional architecture; Zinc oxide nanoparticles